2019
DOI: 10.13057/biodiv/d210116
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of sugar palm (Arenga pinnata) in the Sasak Community, Kekait Village, West Nusa Tenggara, Indonesia

Abstract: Abstract. Haryoso A, Zuhud EAM, Hikmat A, Sunkar A, Darusman D. 2020. Ethnobotany of sugar palm (Arenga pinnata) in the Sasak Community, Kekait Village, West Nusa Tenggara, Indonesia. Biodiversitas 21: 117-128. Sugar palm (Arenga pinnata Merr.) is one kind of palm that has high potential ecological, economic, and socio-cultural values. This Research aimed to identify the ethnobotanical aspects of sugar palm, especially on aspects related to farmers characteristics, cultivation, utilization, cooking process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…At Cai Beo, two types of starches from palms were recovered. The Sugar Palm (Arenga pinnata) is an endemic plant to Southeast Asian countries (Haryoso et al, 2019). In Vietnam, it is grown on the highlands in the central or northern parts of Vietnam (Nguyen et al, 2014).…”
Section: Palmsmentioning
confidence: 99%
“…At Cai Beo, two types of starches from palms were recovered. The Sugar Palm (Arenga pinnata) is an endemic plant to Southeast Asian countries (Haryoso et al, 2019). In Vietnam, it is grown on the highlands in the central or northern parts of Vietnam (Nguyen et al, 2014).…”
Section: Palmsmentioning
confidence: 99%
“…The palm black's fibers, which are locally called ijuk can be use as raw materials for making brooms and water filters. Gunawan et al (2018) and Haryoso et al (2020) reported that there are at least 10 parts of sugar palm that can be used with economic value, namely leaf, young leaf, black fibers, rachis, stalk, bark, inflorescence, trunk/stem, fruit bunch, and root. Moreover, their use is also influenced by the culture, local wisdom, economy, and environment of the region.…”
Section: Multi-utilization and Economic Value Of Arenga Longipesmentioning
confidence: 99%
“…Based on the QDA results, these three samples were characterized by high intensity of ginger aroma, pandan aroma, and palm sugar aroma which may drive consumers' acceptability of bandrek drink. Ginger, pandan, and palm sugar are rich in aromatic compounds and may promote liking [29][30][31][32]. The taste attribute of sample CP was also the most preferred based on consumer test.…”
Section: Consumer Acceptancementioning
confidence: 99%